Textural and compositional evidence for in situ crystallization of palisade bodies in coarse‐grained Ca‐Al‐rich inclusions. (21st February 2019) - Zhang, Mingming; Lin, Yangting; Leya, Ingo; Tang, Guoqiang; Liu, Yu
Abstract: Palisade bodies, mineral assemblages with spinel shells, in coarse‐grained Ca‐, Al‐rich inclusions (CAIs) have been considered either as exotic "mini‐CAIs" captured by their host inclusions (Wark and Lovering1982 ) or as in situ crystallization products of a bubble‐rich melt (Simon and Grossman1997 ). In order to clarify their origins, we conducted a comprehensive study of palisade bodies in an Allende Type B CAI (BBA‐7), using electron backscatter diffraction (EBSD), micro‐computed tomography (Micro‐CT), electron probe microanalysis (EPMA), and secondary ion mass spectrometry (SIMS). New observations support the in situ crystallization mechanism: early/residual melt infiltrated into spinel‐shelled bubbles and crystallized inside. Evidence includes (1) continuous crystallography of anorthite from the interior of the palisade body to the surrounding host; (2) partial consolidation of two individual palisade bodies revealed by micro‐CT; (3) a palisade body was entirely enclosed in a large anorthite crystal, and the anorthite within the palisade body shows the same crystallographic orientation as the anorthite host; and (4) identical chemical and oxygen isotopic compositions of the constituent minerals between the palisade bodies and the surrounding host. Oxygen isotopic compositions of the major minerals in BBA‐7 are bimodal‐distributed. Spinel and fassaite are uniformly 16 O‐rich with ∆ 17 O = −23.3 ± 1.5‰ (2SD), and melilite and anorthite are homogeneously 16 O‐poor with ∆ 17 O = −3.2 ± 0.7‰ (2SD). The latter ∆ 17 O value overlaps with that of the Allende matrix (∆ 17 O ~ −2.87‰) (Clayton and Mayeda1999 ), which could be explained by secondary alteration with a 16 O‐poor fluid in the parent body. The mobility of fluid could be facilitated by the high porosity (1.56–2.56 vol%) and connectivity (~0.17–0.55 vol%) of this inclusion.